Molecular and Physiological Analysis of the Role of Osmolyte Transporters BetL, Gbu, and OpuC in Growth of Listeria monocytogenes at Low Temperatures - Wemekamp-Kamphuis, Henrike H. (American Society for Microbiology, 2004)
Listeria monocytogenes is a ubiquitous food-borne pathogen found widely distributed in nature as well as an undesirable contaminant in a variety of fresh and processed foods. This ubiquity can be at least partly explained by the ability of the organism to grow at high osmolarity and reduced temperatures, a consequence of its ability to accumulate osmo- and cryoprotective compounds termed osmolytes. Single and multiple deletions of the known osmolyte transporters BetL, Gbu, and OpuC significantly reduce growth at low temperatures. During growth in brain heart infusion broth at 7°C, Gbu and OpuC had a more pronounced role in cryoprotection than did BetL. However, upon the addition of betaine to defined medium, the hierarchy of transporter importance shifted to Gbu > BetL > OpuC. Upon the addition of carnitine, only OpuC appeared to play a role in cryoprotection. Measurements of the accumulated osmolytes showed that betaine is preferred over carnitine, while in the absence of a functional Gbu, carnitine was accumulated to higher levels than betaine was at 7°C. Transcriptional analysis of the genes encoding BetL, Gbu, and OpuC revealed that each transporter is induced to different degrees upon cold shock of L. monocytogenes LO28. Additionally, despite being transcriptionally up-regulated upon cold shock, a putative fourth osmolyte transporter, OpuB (identified by bioinformatic analysis and encoded by lmo1421 and lmo1422), showed no significant contribution to listerial chill tolerance. Growth of the quadruple mutant LO28ΔBCGB (ΔbetL ΔopuC Δgbu ΔopuB) was comparable to the that of the triple mutant LO28ΔBCGsoe (ΔbetL ΔopuC Δgbu) at low temperatures. Here, we conclude that betaine and carnitine transport upon low-temperature exposure is mediated via three osmolyte transporters, BetL, Gbu, and OpuC.